2011
DOI: 10.1172/jci58414
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the immunoproteasome subunit PSMB8 causes autoinflammation and lipodystrophy in humans

Abstract: Proteasomes are multisubunit proteases that play a critical role in maintaining cellular function through the selective degradation of ubiquitinated proteins. When 3 additional β subunits, expression of which is induced by IFN-γ, are substituted for their constitutively expressed counterparts, the structure is converted to an immunoproteasome. However, the underlying roles of immunoproteasomes in human diseases are poorly understood. Using exome analysis, we found a homozygous missense mutation (G197V) in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
255
3
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(273 citation statements)
references
References 38 publications
10
255
3
2
Order By: Relevance
“…In different mouse models, the treatment with ONX0914 suppressed autoimmune disease like rheumatoid arthritis, diabetes (Muchamuel et al 2009), colitis , systemic lupus erythematosus (Ichikawa et al 2012), and experimental autoimmune encephalomyelitis (Basler et al 2014). Additionally, this is affirmed by reports that in humans, mutations in the gene encoding for β5i are associated with autoinflammatory disease (Agarwal et al 2010;Arima et al 2011;Kitamura et al 2011). Apparently, the latter regulatory functions of immunoproteasomes are not required in the chicken immune system.…”
Section: Discussionmentioning
confidence: 95%
“…In different mouse models, the treatment with ONX0914 suppressed autoimmune disease like rheumatoid arthritis, diabetes (Muchamuel et al 2009), colitis , systemic lupus erythematosus (Ichikawa et al 2012), and experimental autoimmune encephalomyelitis (Basler et al 2014). Additionally, this is affirmed by reports that in humans, mutations in the gene encoding for β5i are associated with autoinflammatory disease (Agarwal et al 2010;Arima et al 2011;Kitamura et al 2011). Apparently, the latter regulatory functions of immunoproteasomes are not required in the chicken immune system.…”
Section: Discussionmentioning
confidence: 95%
“…The proteasome system is an important nonlysosomal proteolytic pathway that regulates the cell cycle, proliferation, differentiation and inflammation through the selective degradation of ubiquitinated proteins. A previous study has identified PSMB8 as an essential component and regulator of inflammation and adipocyte differentiation, and indicated that immunoproteasomes have pleiotropic functions in maintaining the homeostasis of a variety of cell types 45. PSMB8 expression was first reported as a predictive prognostic factor in gastric cancer 46…”
Section: Discussionmentioning
confidence: 99%
“…51 Application of the PSMB8 selective inhibitor PR-957 in experimental arthritis or colitis could reduce cytokine production and attenuate disease activity. 10,14 On the other hand, the recently described mutations in PSMB8 15,[52][53][54] were all associated with decreased subunit activity and different inflammatory syndromes, suggesting that i-proteasome suppression may cause additional effects depending on dosage and cell type involved. Moreover, influencing antigen processing and presentation through MHC-I may reduce CD8+ T-cell activation but may also increase the risk of tumors, since i-proteasome exerts a fundamental role in tumor rejection 55,56 and of toxicity by accumulating misfolded proteins.…”
Section: Discussionmentioning
confidence: 99%